Formação docente e o ensino de ciências: uma reflexão sobre os anos iniciais - Costa, Jessica Yule da (2024)
The teaching of Science in the early years of basic education is fundamental for the construction of scientific knowledge and for the formation of citizens capable of making informed choices, recognizing the broad connections between science, technology, society, and the environment. The introduction of this knowledge helps build a solid foundation for future studies. However, for this to happen, it is essential that teachers, especially those with a degree in pedagogy, receive adequate training that enables them to teach scientific topics confidently. The presented research aims to analyze and discuss teacher training for Science education at this stage of schooling, based on educators' perceptions. This is a qualitative study whose target audience consisted of teachers from primary schools in the public education system of the metropolitan region of Sorocaba. The study involved 14 teachers from state and municipal schools, who answered a questionnaire about their perspectives on Science teaching, their training, and their classroom practice. The data collected were analyzed using content analysis, contributing to a reflection on the initial and ongoing training of pedagogy graduates for teaching Science. The results indicate that although teachers consider Science education essential, they emphasize the need for more robust training, both initial and continuous, that enables the construction of solid knowledge for effective educational practice, addressing the various areas of scientific knowledge.